A Comprehensive Review on the Therapeutic Potential of Curcuma longa Linn. in Relation to its Major Active Constituent Curcumin - Fuloria, Shivkanya; Mehta, Jyoti; Chandel, Aditi; Mahendran, Sekar; Nur Najihah, Izzati Mat Rani; Begum, M Yasmin; Vetriselvan, Subramaniyan; Chidambaram, Kumarappan; Thangavelu, Lakshmi; Rusli, Bin Nordin; Wu, Yuan Seng *; Kathiresan, V Sathasivam; et al. (Frontiers Media, 2022)
Curcuma longa Linn. (C. longa), popularly known as turmeric, belongs to the Zingiberaceae family and has a long historical background of having healing properties against many diseases. In Unani and Ayurveda medicine, C. longa has been used for liver obstruction and jaundice, and has been applied externally for ulcers and inflammation. Additionally, it is employed in several other ailments such as cough, cold, dental issues, indigestion, skin infections, blood purification, asthma, piles, bronchitis, tumor, wounds, and hepatic disorders, and is used as an antiseptic. Curcumin, a major constituent of C. longa, is well known for its therapeutic potential in numerous disorders. However, there is a lack of literature on the therapeutic potential of C. longa in contrast to curcumin. Hence, the present review aimed to provide in-depth information by highlighting knowledge gaps in traditional and scientific evidence about C. longa in relation to curcumin. The relationship to one another in terms of biological action includes their antioxidant, anti-inflammatory, neuroprotective, anticancer, hepatoprotective, cardioprotective, immunomodulatory, antifertility, antimicrobial, antiallergic, antidermatophytic, and antidepressant properties. Furthermore, in-depth discussion of C. longa on its taxonomic categorization, traditional uses, botanical description, phytochemical ingredients, pharmacology, toxicity, and safety aspects in relation to its major compound curcumin is needed to explore the trends and perspectives for future research. Considering all of the promising evidence to date, there is still a lack of supportive evidence especially from clinical trials on the adjunct use of C. longa and curcumin. This prompts further preclinical and clinical investigations on curcumin.